Effects of Hormonal Contraception on Women of Childbearing Age - Apryanti, Yohana Putri (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2022)
The incidence of cancer in women of childbearing age globally and Indonesia is increasing. The majority of women of childbearing age become users of birth control acceptors, so this study's approval is to determine the effects of hormonal contraception on women of childbearing age. This study uses retrospective methods.   The case group was a woman of childbearing age who became a hormonal birth control acceptor with a sample of 30 respondents. Data analysis using chi-square obtained a value of p = 0.276, meaning there is no meaningful association between hormonal contraception in women of childbearing age and cancer incidence.   The discrepancy of the results of this study with previous research or existing theories may have several possibilities. This can occur in women who use hormonal contraceptives to maintain a healthy lifestyle by maintaining a healthy diet and activity patterns and minimizing the consumption of fatty foods, supported by the nutritional status of women who experience breast cancer normal nutritional status. However, if used for an extended period will also affect the incidence of breast cancer.